Rancang Bangun Pengatur Suhu Kandang Ayam Otomatis Menggunakan Sensor DHT22 Berbasis Wemos D1 R32 Dengan Keluaran Berupa LCD dan Notifikasi Telegram - Mustianto, Fauzan Hendro; Asni Tafrikhatin; Ajeng Tiara Wulandari (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2022)
Temperature fluctuations can cause chicks to experience stress, decreased growth rates, and increased vulnerability to diseases. Manual monitoring and adjustment of temperature in chicken coops require significant manpower and are prone to human errors. Therefore, an automated temperature monitoring process is needed to enhance farming efficiency. This research method utilizes Research & Development. The automatic chicken coop temperature controller utilizes the DHT22 sensor, Wemos D1 R32, LCD, relay, buzzer, LED, incandescent light bulb, DC fan, and Telegram bot. The DHT22 is used as the temperature sensor, while the Wemos D1 R32 acts as the microcontroller. If the temperature exceeds or falls below the predefined limits, the relay connected to the fan or light bulb will turn on or off accordingly, and the results will be sent via Telegram. Based on the test results, the product has an error rate of 4.12%.